Social distancing in a social therapy environment. Issue 3 (4th November 2020) - Akerman, Geraldine Ann; Jones, Emily; Talbot, Harry; Grahame-Wright, Gemma
Abstract : Purpose: This paper aims to describe the impact of the COVID-19 pandemic on a prison-based therapeutic community (TC). Design/methodology/approach: The paper takes the form of a case study where the authors reflect on their current practice, using the findings of research on social isolation and the overarching TC principles to explore the effect of the pandemic on the TC at HMP Grendon. The authors consider how the residents and staff adjusted to the change as the parameters changed when the social distancing rules were imposed and how they adapted to the prolonged break to therapy. Sections in the paper were written by a resident and an operational member of staff. The authors conclude with their thoughts on how to manage the consequences the lockdown has brought and start to think about what returning to "normality" might mean. Findings: The paper describes the adjustments made by the residents and staff as the UK Government imposed the lockdown. The authors, including a resident and an operational member of staff comment on the psychological and practical impact these adjustments had. The thought is given to the idea of "recovery", returning to "normality" and how this study can be best managed once restrictions are lifted. Research limitations/implications: At the time of writing, there are no confirmed cases of COVID-19 at HMP Grendon. The measures and commitment from all staff and residents in the prison to keep the prison environment safe may in part account for this. This paper explores the effects of lockdown on the emotional environment in a TC and highlights the consequences that social isolation can have on any individual. To the authors' knowledge, there is currently no research undertaken on the impact of lockdown/social isolation on a TC. This research would be useful, as the authors postulate from reflections on current practice that the effects of the lockdown will be greater in a social therapy environment. Originality/value: HMP Grendon started in 1962, as this time there have been no significant events that have meant the suspension of therapy for such a sustained period. It is, therefore, important that the impact of such is considered and reflected upon.